Pine Invasions in South America: Reducing Their Ecological Impacts Through Active Management - Pauchard, Aníbal; García, Rafael A.; Zalba, Sergio; Sarasola, Mauro Miguel; Zenni, Rafael; Ziller, Silvia; Nuñez, Martin Andrés (De Gruyter Brill, 2025)
Conifers, and specifically the Pinaceae family, have been one of the most visible and studied plant taxa in invasion biology (e.g., Richardson et al., 1994; Rejmánek & Richardson, 1996; Ledgard, 2001; Essl et al., 2011; Buckley et al., 2005; Gundale et al., 2014). Conifer invasions have several characteristics that make them appealing for ecologists, biogeographers, conservationists, and invasion biologists (Gundale et al., 2014). First, conifers have been widely introduced and extensively planted as a forestry crop and ornamental species all around the world (Richardson, 2006; Simberloff et al., 2010; Essl et al., 2010). Second, most conifer species have attributes associated with high invasiveness such as large propagule production, small seeds, anemochoric dispersal, and broad ranges of climatic and edaphic tolerance (Rejmánek & Richardson, 1996; Essl et al., 2010). Third, conifer invasions are conspicuous in the landscape and can be studied in the field with simple observational techniques (Richardson, 2006; Visser et al., 2014). Fourth, conifer invasions can have severe impacts on the local biota and ecosystem processes such as changes in water and fire regimes (Simberloff et al., 2010). Although conifers have become invasive across the world, the Southern Hemisphere has been especially affected by their establishment and expansion, particularly in the case of Pinus spp. (Simberloff et al., 2010), which, with the exception of one species, did not occur naturally south of the Equator (Lusk, 2008).